IEEE Symposium on Human Centric Computing Languages and Environments, 2003. Proceedings. 2003
DOI: 10.1109/hcc.2003.1260232
|View full text |Cite
|
Sign up to set email alerts
|

An e-whiteboard application to support early design-stage sketching of UML diagrams

Abstract: We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
2

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 12 publications
0
56
0
2
Order By: Relevance
“…Conventional diagramming tools have been shown by many studies to suffer from premature commitment to particular design artefacts and choices; over-constraint of user actions; high viscosity (making designs hard to change); stifling of creativity; and limited collaborative design and review support [29]. As many studies have shown, sketchingbased design tools for a wide range of diagram-centric tasks offer ways of combining the advantages of paperbased and whiteboard-based design with those of computer-based diagramming tools [2,5,7,11,15,20,29]. To date, though, most such research has focused on supporting sketching-based input in a narrow range of design tasks i.e.…”
Section: Motivationmentioning
confidence: 99%
See 4 more Smart Citations
“…Conventional diagramming tools have been shown by many studies to suffer from premature commitment to particular design artefacts and choices; over-constraint of user actions; high viscosity (making designs hard to change); stifling of creativity; and limited collaborative design and review support [29]. As many studies have shown, sketchingbased design tools for a wide range of diagram-centric tasks offer ways of combining the advantages of paperbased and whiteboard-based design with those of computer-based diagramming tools [2,5,7,11,15,20,29]. To date, though, most such research has focused on supporting sketching-based input in a narrow range of design tasks i.e.…”
Section: Motivationmentioning
confidence: 99%
“…Forms3, a spreadsheet style end user programming environment, has been extended with gestural input [4]. Amulet supports gesture-based document manipulation [25] while Knight [8], SUMLOW [5], and Donaldson et al [9] support UML diagram sketching. Most immediately convert sketched input into computer-drawn formalized content.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations